The Impact of Repeated Reading Strategy on Improving Reading Comprehension and Vocabulary Development in English language among Sixth Grade Students in Jordan - Hmeidan, Rula Mohammad Mahmoud (Journal of Educational and Psychological Sciences, 2020)
This study aims to find out the impact of the repeated reading strategy on improving reading comprehension and development vocabulary in the English language of the sixth-grade students in Jordan. The study was applied to 60 students of the sixth-grade students in Wadi Al-Seer secondary girl’s school. On section consisting of 30 students was classified as an experimental group, whereas another section consisting of 30 students was classified as a control group. The experimental group was taught a short story by using the repeated strategy. To measure the effect this story on improving reading comprehension and development vocabulary the researcher used two tools: they are reading comprehension test, which is an essay test consisting of 10 questions and vocabulary test, which also is an essay test consisting of 10 questions. After conducting the study and conducting the appropriate statistical analyses, the results of the study revealed that there is a statistically significant difference at the (α = 0.05) between the two means for the performance of the participants in reading comprehension and vocabulary. This result is ascribed to the teaching strategy and to the group members who received teaching the story by adopting the repeated reading strategy.